The Impact of Fintech on Financial Inclusion and Economic Development - Hîrbu, Ana; Brůna, Karel, 1973-; Šímová, Kateřina; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
The rise of Fintech is an emerging topic as it changes the way financial markets operate. Fintech introduces new business models to the traditional financial industry. The existing literature does not provide sufficient empirical evidence on the significant impact of Fintech on financial inclusion and economic development. Research on this topic has mostly been conducted to analyse the relationship between Fintech and financial inclusion, overlooking the broader impact of digital financial inclusion on overall economic development. This paper aims to bridge this gap by conducting a comprehensive analysis of the evolution of the Fintech sector over the past decade, delving into the correlation between socio-economic indicators and Fintech indicators chronologically, regionally, and quantitatively. This study seeks to understand the intricate interplay between different Fintech tools and financial inclusion, as well as their collective influence on economic development. Moreover, the paper endeavours to empirically investigate the effect of both the traditional and Fintech-based financial inclusion in the group of G22 developing nations, by developing indices of financial inclusion, Fintech and economic development. The findings reveal a robust correlation between Fintech-based financial inclusion and accelerated economic development within the G22 group of developing countries. The experiences of emerging economies will serve as valuable benchmarks for future research, providing indispensable insights for governmental bodies and policymakers in developing nations.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses